2006
DOI: 10.1016/j.rmed.2005.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of low weekly doses of methotrexate in steroid-dependent asthmatic patients. A double-blind, randomized, placebo-controlled study

Abstract: (1) Methotrexate is an effective steroid-sparing agent. (2) A dosage lower than the one recommended in the literature is effective. (3) Tolerance is good. (4) No benefit or detrimental effects in bone metabolism were observed after one year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…There are no clear parameters to guide this decision. Our previous experience with methotrexate 9 showed that some patients may tolerate a period of several months without methotrexate, but that the drug may have to be reintroduced at any time. No clear criteria have been established regarding omalizumab, although some personal experiences seems to show that at least some patients may not tolerate omalizumab withdrawal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no clear parameters to guide this decision. Our previous experience with methotrexate 9 showed that some patients may tolerate a period of several months without methotrexate, but that the drug may have to be reintroduced at any time. No clear criteria have been established regarding omalizumab, although some personal experiences seems to show that at least some patients may not tolerate omalizumab withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients who require frequent or continuous oral corticosteroid administration have received little attention. Due to the severe side effects of steroids when administered over long periods or at high doses, a great deal of effort has been devoted to the search for a possible corticosteroid sparing agent, and many drugs have been assessed to date 9 . The update of the Global Initiative for Asthma Treatment (GINA) report 3 in November 2006 offered for the first time an alternative to oral corticosteroids in patients included in step V (the most severe step).…”
Section: Introductionmentioning
confidence: 99%
“…354,418 Besides sarcoidosis, RCTs have suggested a role for methotrexate as a steroid-sparing agent in chronic asthma. 419,420 Positive effects in open-label trials have also been reported in granulomatosis with polyangiitis for induction of remission in non-life-threatening disease 352,421 or for maintenance of remission after induction with cyclophosphamide. 422 There are also reports of benefi cial effects for cryptogenic organizing pneumonia, 423 polymyositis-dermatomyositis-associated ILD, 424 Churg-Strauss syndrome, 425 and steroidresistant lung allograft rejection.…”
Section: Methotrexatementioning
confidence: 99%
“…cyclosporine or methotrexate have only marginal additive effect. However, where control is difficult despite high dose systemic steroids or when adverse effects of systemic steroids become intolerable, these drugs may prove to have some steroid sparing effect [81]. Adverse effect monitoring is crucial.…”
Section: Managementmentioning
confidence: 99%
“…Adverse effect monitoring is crucial. Methotrexate is given once weekly and close monitoring of blood count is essential [81,82]. With cyclosporine, it important to closely monitor blood pressure and renal function.…”
Section: Managementmentioning
confidence: 99%